Optimalisasi Kemajuan Sequence Penambangan Batubara Seam C Di Pit 1 Utara Banko Barat PT. Satria Bahana Sarana Jobsite Tanjung Enim Mining Operation, Sumatera Selatan - Gamma Putra; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. The stages of mining planning are divided into 3 time periods, namely long term planning, medium term (quarterly plan), and short term planning (daily plan). The current condition of coal mining activities has been above the boundary pit limit so the company will conduct mining in other blocks and the mining will focus on seamless C Pit 1 North for the progress of the next mine. Geotechnical parameters obtained from the bench height of 9 meters wide bench 10 meters with an angle of 450. Road geometry for a straight road 25 meters and for a bend of 29 meters. The results of the Banko West Mine 1 North pit pit reserve design in 2020 obtained 3.404.805 tons of coal and 14.372.990,6 BCM overburden with a stripping ratio of 1: 4,22. The planned production target is determined based on the ability of the main mining equipment each month, namely 2 PC2000 fleets, 3 PC1250 fleets for overburden and 3 PC400 fleets for coal. 15 DT Hino / Fuso (3 fleet PC400) The total cost for coal sales is Rp 3.130.468.832.960,71, for overburden stripping Rp. 553.360.138.100,00 and for coal production costs Rp. 40.857.657.600,00, so mining is feasible.Keywords: Boundary, Bench, Fleets, Pit Reserve, Seam